Novel dental resin infiltrant containing smart monomer dodecylmethylaminoethyl methacrylate - Huang, Xiaoyu; Liang, Jingou; Zhou, Wen; Ma, Tao; Weir, Michael D.; Hack, Gary D.; Fay, Guadalupe Garcia; Oates, Thomas W.; Cheng, Lei; Xu, Hockin H. K. (Frontiers in Cellular and Infection Microbiology, 2022)
Objectives White spot lesions (WSLs) are prevalent and often lead to aesthetic problems and progressive caries. The objectives of this study were to: (1) develop a novel resin infiltrant containing smart monomer dodecylmethylaminoethyl methacrylate (DMAEM) to inhibit WSLs, and (2) investigate the effects of DMAEM incorporation on cytotoxicity, mechanical properties, biofilm-inhibition and protection of enamel hardness for the first time. Methods DMAEM was synthesized using 1-bromododecane, 2-methylamino ethanol and methylmethacrylate. DMAEM with mass fractions of 0%, 1.25%, 2.5% and 5% were incorporated into a resin infiltant containing BisGMA and TEGDMA. Cytotoxicity, mechanical properties and antibacterial effects were tested. After resin infiltration, bovine enamel was demineralized with saliva biofilm acids, and enamel hardness was measured. Result DMAEM infiltration did not increase the cytotoxicity or compromise the physical properties when DMAEM mass fraction was below 5% (p > 0.05). Biofilm metabolic activity was reduced by 90%, and biofilm lactic acid production was reduced by 92%, via DMAEM (p < 0.05). Mutans streptococci biofilm CFU was reduced by 3 logs (p < 0.05). When demineralized in acid and then under biofilms, the infiltrant + 5% DMAEM group produced an enamel hardness (mean ± sd; n = 6) of 2.90 ± 0.06 GPa, much higher than 0.85 ± 0.12 GPa of the infiltrant + 0% DMAEM group (p < 0.05). Significance A novel resin infiltrant with excellent mechanical properties, biocompability, strong antibacterial activity and anti-demineralization effect was developed using DMAEM for the first time. The DMAEM resin infiltrant is promising for inhibiting WSLs, arresting early caries, and protecting enamel hardness.